2014
DOI: 10.1007/s11033-014-3727-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in the development, modification, and prevention of cardiovascular disease

Abstract: Epigenetics has major relevance to all disease processes; cardiovascular (CV) disease and its related conditions are no exception. Epigenetics is defined as the study of heritable alterations in gene expression, or cellular phenotype, and goes far beyond a pure genetic approach. A more precise definition is that epigenetics represents all the meiotically and mitotically inherited changes in gene expression that are not encoded on the deoxyribonucleic acid (DNA) sequence itself. Major epigenetic mechanisms are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 79 publications
0
48
0
Order By: Relevance
“…There is growing evidence suggesting that traits of trainability (the response to exercise training) might depend on epigenetics. Environmental effects, such as nutrition, diet, and exercise can alter epigenetic marks from either DNA methylation or post-translational modifications (acetylation, phosphorylation, and ubiquitination) of histones [124]. One particular study suggests an indirect link between exercise and cardiovascular diseases through epigenetic modulation [124].…”
Section: Epigenetic Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence suggesting that traits of trainability (the response to exercise training) might depend on epigenetics. Environmental effects, such as nutrition, diet, and exercise can alter epigenetic marks from either DNA methylation or post-translational modifications (acetylation, phosphorylation, and ubiquitination) of histones [124]. One particular study suggests an indirect link between exercise and cardiovascular diseases through epigenetic modulation [124].…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…Environmental effects, such as nutrition, diet, and exercise can alter epigenetic marks from either DNA methylation or post-translational modifications (acetylation, phosphorylation, and ubiquitination) of histones [124]. One particular study suggests an indirect link between exercise and cardiovascular diseases through epigenetic modulation [124]. It has also been reported that the myogenic genes in human skeletal muscle are altered by physical activity [125].…”
Section: Epigenetic Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to the epigenome are also associated with the onset and progression of cancer 4,5 and other complex diseases like autoimmune diseases, 6 inflammatory bowel diseases, 7 type 2 diabetes, 8 and cardiovascular disease. 9 Causality of most of these associations remains unknown, but in light of the principal alterability of epigenetic marks-in contrast to the largely stable DNA setup of a cell-, targeting the epigenome may provide a promising strategy in disease therapy and prevention. Major determinants of risk and progression of the above-mentioned common diseases are-besides genetic predispositions-environmental factors like lifestyle and diet.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetics is the way environment influences the expression of DNA; it does not alter the DNA sequence, but it can be heritable [7], changes include DNA methylation, histone modifications, and chromatin remodeling. Many fine studies have shown the influence of environment on DNA for embryonic development; but also for the future development of obesity or diabetes, for the development of stress responses, of hypertension or cancer.…”
Section: Introductionmentioning
confidence: 99%